KEBIJAKAN HUKUM PEMERINTAH KABUPATEN BANTUL DALAM PENANGANAN PERKARA PROSTITUSI - Sri Hendarto Kunto Hermawan (Kajian Hukum, 2016)
The policy in the field of criminal law is very important, especially in an increasingly modern life as a result of globalization, therefore, in the progress necessary to find alternative ways of law enforcement more precise and faster. The Book of Criminal Justice Act which is a relic of the Dutch era, which has been deemed incompatible with existing development, therefore, with the plan to change the existing Criminal Code and Criminal Procedure Code is a positive step. Similarly, the policy of the law made by the Government of Bantul district in addressing the problem of prostitution, set Bantul Regency Regulation No. 5 Year 2007 on the Prohibition of Prostitution in Bantul is a form and the efforts made by the District Government of Bantul to combat and reduce the occurrence of cases prostitution and prostitution. This was done considering the Bantul district has the south sea coast which many practices used for prostitution, as well as the construction of inns, karaoke bars and massage parlors and beauty salons, there are times when these places abused. Therefore, law enforcement efforts undertaken by law enforcement officers must be fully supported. Bantul District Government legal policies that are already well underway and effective, proven cases that occur are increasingly declining, this happens because the vigorous enforcement efforts conducted by the Pamong Praja Police Unit of Bantul District supported by officers from the Police Bantul, either that individually or in combination with the Municipal Police Unity with police.